2020
DOI: 10.1159/000507952
|View full text |Cite
|
Sign up to set email alerts
|

Material Risks of Homeopathic Medicinal Products: Regulatory Frameworks, Results of Preclinical Toxicology, and Clinical Meta-Analyses and Their Implications

Abstract: Homeopathy is widely used and broadly accepted by health care professionals and the general public but less in academic circles. To assess possible material health risks of homeopathic medicinal products, it is necessary to identify, select, and synthesize the findings of recent reviews of controlled homeopathic clinical trials. Matching these findings with experimental data from toxicological studies helps to clarify what is known and not known about the material risks of homeopathic medicines. Rules for toxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…However, due to their increased use and high demand, homeopathic medicines have been the subject of some public and government concerns regarding their safety. 3 4 5 6 Furthermore, it has been found that homeopathic medicines are commonly prescribed without scientific evidence or knowledge of any toxicological effects they might possess. Despite the fact that homeopathic medicines are often used at extremely high dilutions, further research into their toxicity is currently required.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to their increased use and high demand, homeopathic medicines have been the subject of some public and government concerns regarding their safety. 3 4 5 6 Furthermore, it has been found that homeopathic medicines are commonly prescribed without scientific evidence or knowledge of any toxicological effects they might possess. Despite the fact that homeopathic medicines are often used at extremely high dilutions, further research into their toxicity is currently required.…”
Section: Introductionmentioning
confidence: 99%
“…mostly of developing countries relies on nonconventional medicine in their primary health care. With the growing market demand and the worldwide increase in the use of Homoeopathic medicines, health authorities -and consumers -are quite concerned with their safety (Briggs et al, 2003;Organization, 2009;Singh et al, 2014;Habs et al, 2021). Homeopathic medicines are typically administered are at high ultra dilution, are often thought to present no major safety concerns.…”
Section: Introductionmentioning
confidence: 99%
“…3 A recent meta-analysis found no differences in the frequency of adverse reactions between homeopathic and placebo treatments. 4 Even NHS, a source quoted by the authors in the paper, reports Homeopathy to be safe. 5 As such, in the nine cases of drug-induced hepatotoxicity, it needs to be identified if: The drugs were indeed homeopathic drugs.…”
mentioning
confidence: 99%